SIKAP POLITIK KEPALA DESA DALAM MEWUJUDKAN GOOD GOVERNMENT DI DESA TANDA RAJA KECAMATAN KIKIM TIMUR KABUPATEN LAHAT - Wulan Puji Lestari; Izzomiddin Izzomiddin; Norma Juainah (Jurnal Prodi Ilmu Politik, 2023)
ABSTRACT This Article discusses about The Performance Of The Village Head in Realizing Good Government in the Village Of Tanda Raja, East Kikim District, Lahat Regenncy. This study uses qualitative research methods, the data obtained through direct interviews with several informants in the village of Tanda Raja. This study aims to determine the attitude of the village head in realizing good government in the village of Tanda Raja and to find out what are the inhibiting factors of the village head and the community in realizing good government. This study uses the theory of political behavior by Harold D. Lasswell, which theory is closely related to the political behavior of village heads. The results of this study are that the political behavior of the village head through his conversations perceptions, attitudes, is inseparable from the vision, mission and program aspects. So that it can be accordance with the duties and obligations. The second is the inhibiting factor in realizing good government, namely human resources that are still lacking, lack of village office facilities, and internet networks that are not yet possible. Value oriented political behavior or trying to achieve goals. Values and goals are formed in the process of political behavior, which is actually a part. Second, political behavior aims to reach the future, is anticipatory, relates to the past and always pays attention to past events.